Pengembangan Modul Pembelajaran Konsep Esensial Geografi dalam Pembelajaran IPS di Sekolah Menengah Pertama - Lestariningsih, Dwi Sukanti; Munandar, Aris; Azzahra, Anisa (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
The purpose of this study was to find out "Is the Infographic on the Development of Essential Geography Concepts practical and effective for Social Studies Learning in Junior High Schools". The methodology used in this research is Research and Development (R&D), with data collection techniques through literature studies, documentation and interviews as well as assessments from Social Sciences (IPS) subject teachers to gain a deep and comprehensive understanding of the Essential Concepts Geography in social studies syllabus. The development research that will be carried out is to develop an infographic product with the essential concept of geography. The results of the study show that infographics about the Essential Concepts of Geography are guided by KD 3.1 and KD 4.1 in the 2013 social studies curriculum for grades VII, VIII, and IX with themes. In class VII, the theme is Dieng Plateau and Community Activities in the Surrounding Areas. In class VIII, the theme is Spatial Change and Indonesia's Interaction with ASEAN Countries. In class IX, the theme is Spatial Change and Interaction with ASIA Countries. Thus, the use of infographics in the development of social studies subject matter on the Essential Concepts of Geography for teachers is very important, practical and effective in junior high schools.